Measuring self-control in a wild songbird using a spatial discounting task - Ella McCallum; Rachael C. Shaw (Animal Cognition)
Abstract Self-control allows animals to resist instant gratification and invest more time and/or energy in better outcomes. However, widespread temporal self-control tasks lack ecological validity for many species, and few studies have explored whether self-control can be measured in the wild. We used a spatial discounting task resembling natural foraging decisions to measure self-control in wild toutouwai (Petroica longipes), a songbird endemic to New Zealand. Birds chose between a near, low-quality food item and a high-quality food item further away. Toutouwai showed striking individual variation in their self-control abilities. Validation tests suggested that our task reliably measured self-control in a spatial foraging context. However, individual-level performance was confounded by food preferences and the satiation and/or learning effects associated with increasing trial number, limiting the applicability of this task as a measure of individual variation in self-control. Nonetheless, we found no correlation between an individual’s self-control and their inhibitory control measured using a detour task, suggesting that self-control is a distinct ability from the suppression of impulsive motor actions in toutouwai. This study demonstrates for the first time that a bird is capable of self-control in a spatial context and provides suggestions for how future researchers may robustly quantify individual differences in self-control in the wild.